U źródeł społecznej myśli Kościoła - GROSFELD, Jan (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
The article comprises a presentation of the original sources of the aspects of the magisterium (and of the broader reflection of the Church) which are commonly known as social teaching. Briefly speaking, the ultimate source of the social teaching of the Church, as well as its inspiration, lies in the Good News itself, which, already in its essence, is addressed directly to the human person. The anthropological vision inherent in the Gospels and in the entire New Testament must encourage the communitarian and social functioning of the human being, which is inscribed in the human nature itself. Thus this vision of the human person reaches deep into the existential condition, and unlike other approaches, offers not only a diagnosis, but also a serious treatment of the plight human life involves. The recovery may be accomplished by means of following the way Jesus Christ had followed: it involves the realization of «who I am» (kenosis) and the experience of the unconditional love God offers. Only by following this way, can human beings overcome the captivity resulting from their fear of death (St. Paul). Against the opinion of the world, to consider oneself weak, guilty and helpless is the only way that makes it possible to accept the grace of forgiveness, together with the love and omnipotence of God. Egoistic and individualistic attitudes prevent human beings from overcoming the circle of fear and impossibility. Today’s crisis of the Church, connected to the crisis of our civilization, provides an opportunity to reach to the roots of the Christian faith – also to the Jewish ones – and to reformulate the mission of the Church in the radically new cultural situation. Poverty in spirit and witness to the personal and communal experience of the living God and Jesus Christ are conditions of the revitalization of the Church and simultaneously the way towards its renewal. Translated by Dorota Chabrajska